Satisfying Our Common Lots Without Despoiling Our Natural Domicile: All Hands on Deck. (International Journal of Scientific Research and Management (IJSRM), 2022)
In a competitive world, development and the environment are closely intertwined. Development cannot stop for the sake of the environment. The environment is the only pathway from which we draw our sustenance. It is, therefore, an indisputable fact that our very survival depends on the environment. The problem arises when attempting to satisfy our insatiable needs whilst subjecting other components of the earth system into perpetual savagery. That said, the focus of this paper is to stress the need to integrate environmental considerations into our everyday lives. This paper has carefully articulated the concepts of environment and development by contributing to the debate of development without running into resource constraints. Furthermore, environmental thoughts have also been enunciated to season the arguments.